Column Chromatography Fractionation and Antioxidant Activity of Passiflora foetida Leaves - Nita Triadisti; Irfan Zamzani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Available synthetic antioxidants have been reported to have mutagenic and toxic effects. On the other hand, natural antioxidants show their superiority as they are not or less toxic. Passiflora foetida has the potential as an antioxidant, but the investigation of the antioxidant activity of the P. foetida chromatography column fraction has not been reported. This studied aims to investigate the antioxidant activity of the column chromatographic fractions of P. foetida leaves. An antioxidant assay using the DPPH and FRAP methods. The extraction was carried out by graded maceration, then fractionation using column chromatography. The antioxidant activity test was carried out using the DPPH and FRAP methods. Thin Layer Chromatography analysis was performed to determine the chromatogram pattern. The EC50 using DPPH method from n-hexane extract: 129.035 µg/mL, ethyl acetate extract: 206.398 µg/mL, methanol extract: 97.453 µg/mL, while the EC50 using FRAP method from n-hexane extract: 67.851 µg/mL, ethyl acetate extract : 68.981 µg/mL, and methanol extract: 58.787 µg/mL. Column chromatography fractions have antioxidant activity, with FMetPF6 as the fraction with the best activity, with percent inhibition 41.85±1.96 at concentration 25 µg/mL (DPPH), and with percent antioxidant activity 26.03±0.84 at concentration 9 µg/mL (FRAP). Passiflora foetida leaves have great potential as an antioxidant; both the extract and its fractions have antioxidant activity. The FMetPF6 has the best activity compare to other extracts and fractions. Further analysis to determine the various compounds in FMetPF6 using LC-MS/MS will facilitate the active compound's isolation.